How to stop losing your sh*t with your kids ebook A practical guide to becoming a calmer, happier parent. - Naumburg, Carla (2019)
Stop the yelling, lose the guilt, and become a calmer, happier parent.   Drawing on evidence-based practices, here is an insight-packed and tip-filled plan for how to stop the parental meltdowns. Its compassionate, pragmatic approach will help readers feel less ashamed and more empowered to get their, ahem, act together instead of losing it.   “Using a powerful combination of humor and reality checks, Naumburg helps parents unpack their unique stressors (we all have them) and find ways to stay calm even the most frustrating of family moments.” —Katie Hurley, LCSW, author of No More Mean Girls and The Happy Kid Handbook   “By the end not only are you laughing out loud, but you’ve gained a sense of self-compassion and a concrete action plan.”—Rebecca Schrag Hershberg, PhD, author of The Tantrum Survival Guide